DRIFT GILL-NETTING IN LOWER SUNDARBANS, WEST BENGAL - Banerjee, M K; Chakraborti, R D (Indian Journal of Fisheries, 2011)
Fishing trials were made in the Lower Sundarbans to study the effectiveness of .threedifferentmeshsizes(88,mm, 101 nimandll4mm)of gillnetsin the capture of fishes of conunercial importanc;. Seventy per cent of the catches were sharks. Both Hilsa ilisha and Scomberomorus guttatus were mainly gilled by the 89-mm meshes, whereas the 101-mm meshes were more effective for Chirocentms dorab and Pampus argenteus. Majority of fishes captured were entangled mainly inthe 101-mm-ijieshed nets.